Tinjauan Etika Profesi dan Independensi Auditor dalam Mempertahankan Kualitas Audit di Era Digital - Nastiti Handayani; Nazila Aolivia Hindana; Uswatun Khasanah; Fikri Rizki Utama (Indo Publishing, 2026)
The development of Artificial Intelligence (AI) and Big Data Analytics (BDA) has transformed modern auditing practices by improving efficiency, accuracy, and data analysis capabilities. However, the digitalization of auditing also presents challenges to professional ethics and auditor independence, particularly regarding automation bias, data confidentiality, and the decline of professional skepticism. This study aims to analyze the influence of AI and BDA implementation on professional ethics, auditor independence, and audit quality in the digital era from the perspective of Islamic accounting. This research employs a qualitative approach with a descriptive-qualitative design. Data were collected through semi-structured interviews, observations, and documentation involving 12 informants consisting of public accounting firm auditors, academics in auditing and Islamic accounting, and audit technology practitioners in Indonesia selected using purposive sampling techniques. Data analysis was conducted systematically through data reduction, data presentation, and conclusion drawing. The findings indicate that AI and BDA are capable of improving audit quality through increased audit efficiency, more accurate analytical processes, and faster risk detection capabilities. Nevertheless, the use of technology also creates risks of excessive dependence on automated systems and data security threats if not supported by adequate technological competence and the strengthening of auditors’ professional ethics. The novelty of this study lies in the integration of digital auditing, auditor independence, and Islamic accounting values within a comprehensive framework. This study implies the importance of strengthening digital literacy, data security, and digital audit ethical standards, although the findings remain limited to a specific context and number of informants.